Determinación del nivel de parasitoidismo en lepidópteros y coleópteros en un de Bosque Andino a distintos niveles de recuperación. - Jiménez Alvarez, María del Cisne (2018)
The Andean forest ecosystems, in spite of their great ecosystemic importance, have been degraded in their great majority due mainly to the anthropogenic activity such as deforestation, burning of forests, invasion of exotic species, among others. An ecosystem with diverse processes of disturbance leads to the loss of biodiversity and to the alteration of the essential ecosystem functions for the proper functioning of the ecosystem. One of the most sensitive functions corresponds to parasitoidism, the biological association between a parasitoid insect and another host, for its action in the regulation of populations. In the present study, the level of parasitoidism was related to the state of recovery of an Andean forest ecosystem in the city of Loja in two study areas, the El Madrigal Reserve and the PUEAR. Three levels of recovery were determined (PB, ZAR and ZMR), and five common plant species in each study area for the collection of larvae and pupae of Lepidoptera and Coleoptera. After the breeding of larvae and pupae in the laboratory phase, the adult individuals of each order were counted for the calculation of the parasitoidism rate. A total of 172 individuals of larvae and pupae were collected, obtaining a general parasitoidism rate of 65.53%., A medium to high level of parasitoidism in both study areas. Alnus acuminata was the plant species that presented a higher rate of parasitoidism in the El Madrigal Reserve and in the PUEAR. In the comparative statistical study between the levels of recovery, the rate of parasitoidism and the vegetal species it was evidenced that there are no statistically significant differences in any of the study areas, reason why it is believed that the parasitoidism function is in a good recovery process. In addition, there was a negative correlation between the parasitoid function and the diversity of parasitoids. It is concluded that the levels of parasitoidism within this study could be affected not only by the diversity and abundance of parasitoids, but also by the structure and variability of the food webs in which it is immense. Keywords: Andean forest; recovery levels; parasitoidism; larvae and pupae; Hymenoptera parasitoids.